2013
DOI: 10.1177/0748233713499600
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of pomegranate juice consumption on carbon tetrachloride-induced sperm damages, lipid peroxidation, and testicular apoptosis

Abstract: The aim of this study was to investigate whether pomegranate juice (PJ) consumption has an ameliorating effect on carbon tetrachloride (CCl4)-induced sperm damages and testicular apoptosis associated with the oxidative stress in male rats. The study comprised of four groups (groups 1-4). Group 1 received olive oil + distilled water daily; group 2 was treated with 5 ml/kg PJ + olive oil daily; group 3 was treated with 0.25 ml/kg CCl4 dissolved in olive oil, weekly + distilled water daily; and group 4 received w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
(95 reference statements)
1
15
0
1
Order By: Relevance
“…19,22,23 Environmental pollutants, such as carbon tetrachloride, 2,3,7,8-tetrachlorodibenzo-pdioxin and polychlorinated biphenyl, can result in testicular histopathological lesions and decreased reproductive organ weights. [24][25][26][27][28] In the present study, PFOA-induced testicular damage in mice was evidenced by decreased testicular weight, reduced epididymal sperm count and disorganized seminiferous epithelium, which might be consequences of elevated oxidative stress and excessive apoptosis in the testis. It has been demonstrated that PFOA exposure reduces testosterone biosynthesis and production.…”
Section: Discussionsupporting
confidence: 46%
“…19,22,23 Environmental pollutants, such as carbon tetrachloride, 2,3,7,8-tetrachlorodibenzo-pdioxin and polychlorinated biphenyl, can result in testicular histopathological lesions and decreased reproductive organ weights. [24][25][26][27][28] In the present study, PFOA-induced testicular damage in mice was evidenced by decreased testicular weight, reduced epididymal sperm count and disorganized seminiferous epithelium, which might be consequences of elevated oxidative stress and excessive apoptosis in the testis. It has been demonstrated that PFOA exposure reduces testosterone biosynthesis and production.…”
Section: Discussionsupporting
confidence: 46%
“…Administration of fruit juice to male Wistar rats showed significant improvement in sperm parameters compared to control group (Turk et al., ). Daily consumption of this juice improved sperm cell abnormalities following testicular torsion–detorsion and carbon tetrachloride intoxication in rats (Al‐Olayan et al., ; Atilgan et al., ; Dkhil et al., ; Turk et al., , ). Moreover, fruit juice showed protective effect against structural sperm changes induced by bisphenol A (El Ghazzawy et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation is the chief oxidative stress effect and most prevalent form of oxidative stress compromise at cellular level; it is a toxic process to the cells causing cell loss of membrane integrity, cell death and activation of genetic programme cell death [33]. Compromised reproductive inefficiencies in male such as spermatozoa dysfunctions, low epididymis sperm concentrations, poor sperm motility and abnormal sperm morphology are also linked with increasing lipid peroxidation [34]. In female, infertility triggered by endometriosis is also reportedly linked with increased production of oxidative stress products specifically increasing levels of malondialdehyde; furthermore, lipid peroxidation is also mechanism of oxidative stress associated withdecline oocytes quality [35, 36].…”
Section: Discussionmentioning
confidence: 99%